SODIUM NITRITE (E250) AND ZINC AS MODULATORS OF THE BIOMECHANICAL PROPERTIES OF BLOOD IN SPORTS - Ivan M. Ivanov; Yordanka Gluhcheva; Emilia Petrova (Scientific Publishing House. NSA Press, 2024)
Nutritional supplements are often used by athletes to support their performance. However, if there is no nutrient deficiency, supplementation may not improve performance and may even have a detrimental effect on both performance and health. The aim of this study was to review the influence of sodium nitrite (NaNO2) and zinc (Zn) on the hemorheological status of different types of blood cells with application in sports. Sodium nitrite, known as food preservative E250, and zinc are proven modulators of the biomechanical properties of blood, influencing its hematometric and hemorheological properties. Our previous experimental results demonstrated that intraperitoneal injection of NaNO2 in mature rats had a diverse effect on the leukocyte and platelet populations. After the treatment, the number of monocytes and granulocytes decreased significantly, thus increasing the susceptibility to infections. The number of platelets increased, altering the coagulation status of blood. Scientific research data show that the proper intake of NaNO2 and Zn improves glucose metabolism, a key factor in maintaining energy levels during physical activity, muscle strength, and endurance. Zn also exhibits protective effects against bone loss. Excessive intake of zinc for long periods may interfere with other essential elements of metabolism. This review proves that hemorheological parameters such as whole blood viscosity, plasma viscosity, as well as the main hematometric indices are suitable quantitative biological markers for monitoring nitrite and/or zinc supplementation.